Surface Engineering and Built‐In Electric Field within Copper Sulfide/Graphitic Carbon Nitride Photocatalyst for Extremely Enhanced Charge Separation and Broad‐Spectrum Pharmaceuticals and Personal Care Products Degradation. Issue 1 (20th November 2020) - Zhang, Linlin; Sun, Wei; Ge, Chengjun; Liao, Jianjun
Abstract : Semiconductor photocatalysis is the most commonly used technology for the photocatalytic degradation of pharmaceuticals and personal care products, but it suffers from fast charge recombination and a low degradation efficiency. Herein, a novel photocatalyst is synthesized by anchoring copper sulfide nanoparticles on oxygen‐doped graphitic carbon nitride hollow nanospheres. g‐C3 N4 is bent to form a nanosphere structure, which promotes the interlayer photogenerated charge transfer, improves the specific surface area, and provides more reaction sites. Moreover, the hollow structure can enhance the utilization of light through the reflection and refraction of light in the cavity. The hollow nanospheres structure has a large number of reaction sites and enhanced light absorption due to internal reflection. After the introduction of copper sulfide, a built‐in electric field is formed, which improves the separation and transmission of photogenerated carriers, and extends the light response range into the near‐infrared (NIR) region. Consequently, the photocatalytic degradation efficiency of phenol and diclofenac reach 100% after vis–NIR irradiation for only 25 and 30 min, respectively. The radical trapping experiments and electron spin resonance analysis show that O2 − plays an important role in the photodegradation process. This work provides a strategy for constructing broad‐spectrum response photocatalysts. Abstract : Cu2– x S/O‐HC3 N4 exhibits remarkably enhanced vis–NIR photocatalytic activity for the degradation of pharmaceuticals and personal care products (PPCPs). Benefiting from the hollow and nanosphere structure, the composite provides more reaction sites and enhances the utilization of light for photocatalytic reaction. In addition, the built‐in electric field formed by Cu2– x S and O‐HC3 N4 accelerates the electron transport between the heterojunction interfaces.